The Influence of Spokesperson Trustworthiness on Message Elaboration, Attitude Strength, and Advertising Effectiveness - Priester, Joseph R.; Petty, Richard E. (Journal of Consumer Psychology, 2003)
Recent research has shown that information presented by untrustworthy endorsers is likely to be thoughtfully elaborated, whereas information presented by trustworthy endorsers is likely to be unthinkingly accepted (Priester & Petty, 1995). Study 1 manipulated argument quality and assessed cognitive responses to demonstrate that this influence of trustworthiness on persuasion holds for familiar endorsers likely to be used in actual advertisements. Study 2 demonstrated that trustworthiness can be influenced by individuals endorsing too many products, with similar persuasion consequences (i.e., untrustworthy endorsers prompt greater scrutiny of product‐related attributes than trustworthy endorsers). Study 2 also found that the attitudes that resulted from an untrustworthy endorser came to mind faster, even when those attitudes were equivalently positive—thus demonstrating that elaboration can influence attitude accessibility. This research provides evidence that attitude extremity may not be a sufficient indicator of advertising effectiveness, in that equally extreme attitudes can vary as to the bases by which they were formed, their underlying strength, and their effectiveness. Further, this research provides theoretical and strategic insight into the use of trustworthy and untrustworthy endorsers.